Preparation of CoFe2O4/SiO2/Ag Magnetic Composite as Photocatalyst for Congo Red Dye and Antibacterial Potential - Salni Salni; Muhammad Said; Eliza Eliza; Anggun Dita Dyah Gayatri; Poedji Loekitowati Hariani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
This research reports the synthesized CoFe2O4/SiO2/Ag magnetic composite used as a photocatalyst to degrade Congo red dye and antibacterial agent against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The catalysts were characterized using XRD, SEM-EDS, VSM, UV-DRS, and pHpzc. The effects of photocatalyst dose (0.25, 0.5, 0.75, and 1.0 g/L), dye concentration (10, 20, 30, and 40 mg/L), and irradiation time (0–210 minutes) were all examined as photocatalytic degradation variables. The results showed that the CoFe2O4/SiO2/Ag composite was superparamagnetic with a saturation magnetization of 41.82 emu/g and had a band gap of 1.82 eV. The highest efficiency of decreasing the concentration of Congo red dye of 93.70% was obtained with an initial concentration of 10 mg/L, a catalyst dose of 0.5 g/L, and an irradiation time of 180 minutes. This study indicated that the composite had antibacterial properties against Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria with the same MIC value of 1.25%. These results indicated that the CoFe2O4/SiO2/Ag composite has significant potential for applications in wastewater treatment.